Trabalho, meio ambiente e desenvolvimento sustentável: implicações para uma proposta de formação crítica - Deluiz, Neise; Novicki, Victor (Boletim Técnico do Senac, 2004)
This article focuses on the relations between work, environment, and education in the context of capitalist internationalization. It analyzes reflections about the impact of the neoliberal globalization process on the spheres of production, work, and the environmental crisis. It also discusses the theoretical and conceptual matrices that guide the different sustainable development projects being debated in contemporary society. The article assumes the perspective of “democratic sustainability” and seeks to point out guiding principles for a democratic proposal to educate critical and autonomous subjects.